A Targumist interprets the Thora contradictions and coherence in Targum Pseudo-Jonathan - Zhakevich, Iosif J. (Boston BRILL, 2022)
This book conducts a study of contradictions and coherence in Targum Pseudo-Jonathan and suggests that the alleged contradictions are ultimately given to resolution, once the greater context of biblical and Jewish tradition is taken into consideration.
Intro -- ‎Contents -- ‎Acknowledgments -- ‎Figures and Tables -- ‎Abbreviations -- ‎Introduction -- ‎1. Overview -- ‎2. Methodology -- ‎3. A Brief History of Research -- ‎4. Primary and Secondary Sources -- ‎Part 1. Vertical Dimension-Contradictions between the Torah and the Targum -- ‎Chapter 1. Contradictions in Converse Translation I -- ‎1. Introduction -- ‎2. Creation of the Rhetorical Question: Genesis 4:14 -- ‎3. Addition of the Negative Particle I: Genesis 4:23-24 -- ‎4. Addition of the Negative Particle II: Genesis 37:33 -- ‎5. Replacement of the Verb: Exodus 33:3-5 -- ‎6. Conclusion -- ‎Chapter 2. Contradictions in Converse Translation II -- ‎1. Introduction -- ‎2. Elimination of the (Implied) Negative Particle at TgPsJ Genesis 19:33 -- ‎3. Three Questions Regarding the Converse Translation at TgPsJ Genesis 19:33 -- ‎4. Modern Scholarship on the Converse Translation at TgPsJ Genesis 19:33 -- ‎5. A Deliberate Converse Translation at TgPsJ Genesis 19:33 -- ‎6. The Mechanism of Derivation of the Converse Translation at TgPsJ Genesis 19:33 -- ‎7. The Discrepancy between the Manuscript and the Printed Editions at TgPsJ Genesis 19:33 -- ‎8. Conclusion -- ‎Part 2. Horizontal Dimension-Contradictions between Passages within the Targum -- ‎Chapter 3. Contradictions in the Targum I-Concerning Numerals -- ‎1. Introduction -- ‎2. Part I: Contradictions with Explicit Reference to Numerals -- ‎2.1. The Number of Plagues in Egypt: Genesis 15:14 vs. Exodus 14:21 -- ‎2.2. The Duration of the Barrenness of Isaac and Rebekah: Genesis 25:20-26 -- ‎2.3. The Duration of the Famine in Egypt: Genesis 41:27, 30 vs. 50:3 -- ‎3. Part II: Contradictions with Implicit Reference to Numerals -- ‎3.1. The Chronology of Isaac's Life: Genesis 35:29 vs. 37:35 -- ‎3.2. The Chronology of Abraham's Life: Genesis 25:8 vs. 25:29.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books